2016
DOI: 10.1186/s13062-016-0142-5
|View full text |Cite
|
Sign up to set email alerts
|

Optimal treatment and stochastic modeling of heterogeneous tumors

Abstract: In this work we review past articles that have mathematically studied cancer heterogeneity and the impact of this heterogeneity on the structure of optimal therapy. We look at past works on modeling how heterogeneous tumors respond to radiotherapy, and take a particularly close look at how the optimal radiotherapy schedule is modified by the presence of heterogeneity. In addition, we review past works on the study of optimal chemotherapy when dealing with heterogeneous tumors.Reviewers: This article was review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 93 publications
(128 reference statements)
0
7
0
Order By: Relevance
“…Each progenitor cell bears the mutation and phenotypic profile of the parent cell and is capable of reconstituting a tumor. Several studies have since challenged this theory by demonstrating the existence of a subpopulation of cells called cancer stem cells (CSCs) or tumor-initiating cells, which are typically quiescent but under certain conditions, capable of proliferating to self-renew the CSC population and generate progenitor tumor cells ( 3 , 4 ). CSCs are resistant to therapies that target rapidly proliferating tumor cells and are primarily responsible for tumor relapse.…”
Section: Introductionmentioning
confidence: 99%
“…Each progenitor cell bears the mutation and phenotypic profile of the parent cell and is capable of reconstituting a tumor. Several studies have since challenged this theory by demonstrating the existence of a subpopulation of cells called cancer stem cells (CSCs) or tumor-initiating cells, which are typically quiescent but under certain conditions, capable of proliferating to self-renew the CSC population and generate progenitor tumor cells ( 3 , 4 ). CSCs are resistant to therapies that target rapidly proliferating tumor cells and are primarily responsible for tumor relapse.…”
Section: Introductionmentioning
confidence: 99%
“…We performed a control run with untreated but irradiated cells, which revealed that our cells hardly respond at all to radiotherapy after 24 hours. Response to radiotherapy of HNSCC increases according to a linear‐quadratic model with dose and time after treatment . This might be an explanation for the effect in this study, as radiosensitizing effect occurs only in the long term.…”
Section: Discussionmentioning
confidence: 65%
“…Response to radiotherapy of HNSCC increases according to a linear-quadratic model with dose and time after treatment. 30,31 This might be an explanation for the effect in this study, as radiosensitizing effect occurs only in the long term.…”
Section: Discussionmentioning
confidence: 73%
“…Only the complete extinction of the CSCs population would completely eradicate the tumor [ 100 , 101 ]. Alternatively, if we consider the stochastic model in which each cell can be tumour-initiating, the path to eradicating the tumor is much more complicated [ 102 ]. Olmeda et al put forth a tumor initiation model comprised of CSCs, differentiated cancer cells, and all the other cells within a tumour [ 103 ].…”
Section: Cscs Are the Key Drivers Of Tumor Initiation And Progressionmentioning
confidence: 99%
“…The CSC initiation process is stemness transcription factors dependent that drive the expression of genes not expressed in normal cells but is highly expressed in CSCs, especially during the initiation process [ 102 104 ]. Blanpain et al demonstrated a vital role for the transcription factor sex-determining region Y-Box 2 (SOX2) in the melanoma initiation and progression [ 105 , 106 ].…”
Section: Cscs Are the Key Drivers Of Tumor Initiation And Progressionmentioning
confidence: 99%